MARKETING MIX IN THE DIGITALIZATION AGE - Abdul Hakim (ADISAM Publisher, 2022)
One of the important keys in business competition in the modern industrial era is being able to create a product or service that is able to meet the needs and desires of consumers. The importance of this issue makes all large and small companies and even micro business actors make various efforts in order to win the hearts of consumers and try to provide maximum satisfaction for their consumers. In its application, marketing has several variables that are integrated with each other and affect the success of its application